PENGGUNAAN METODE TANYA JAWAB TEKNIK TONGKAT BERBICARA (TALKING STICK) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI KELAS X.2 SMAN 1 KAMPAR KIRI HILIR: (The Use of Question an Answer Method of Talking Stick (Talking Stick) to Improve Student Learning Outcomes In Economic Subject at Class X.2 SMA Negeri 1 Kampar Kiri Hilir) - Tity Hastuti; Agus Baskara; Wulan Purnama Sawitri (Perspektif Pendidikan dan Keguruan, 2015)
The purpose of the writing of this study is as one alternative solution of the problems faced by the parties with an interest in improving the quality of the learning economy through the use of question and answer technique of talking stick (talking stick). The subject of this research is class student of SMA X.2 Kampar Kiri Hilir numbering as many as 25 students. The approach used in this study was classroom action research (PTK), each cycle consisting of planning, implementation, observation, and reflection, research conducted by two cycles, each cycle is 2 meetings with one test. This study was conducted from March to April 2015 will be applied to the subject of understanding the economic problems in relation to human needs, scarcity and economic system. The results showed that the method of question and answer with the talking stick technique can improve learning outcomes Economic X.2 grade students of SMA Negeri 1 Kampar Kiri Hilir. This method has been applied with the talking stick as possible so as to increase the activity of teachers in the first cycle 18 (quite perfect), to two 23.3 (perfect). Then student activity was also seen in the first cycle is 83%, and in the second cycle of 89%.